The physico-chemical properties of electrospun vascular PLLA scaffolds modified by the DC magnetron sputtering of a titanium target; Journal of Physics: Conference Series; Vol. 1115 : 6th International Congress "Energy Fluxes and Radiation Effects". 14th International Conference on Modification of Materials with Particle Beams and Plasma Flows (14th CMM) - Marjin (Maryin) P. V. Pavel Vladimirovich (2018, 2018)
Title screen